(untitled) (Bangladesh Medical Journal, 2022)
Pachydermoperiostosis (PDP) is a rare autosomal disorder characterized by periostosis, clubbing, thickening of the skin (pachyderma) of the face and scalp, seborrhea and hyperhydrosis. It is the primary form of hypertrophic osteoarthropathy (HOA), the other name of which is Touraine- Solente-Golé syndrome. PDP has various organ involvements and there are some rare associations of PDP with other disorders. Here we describe a 16-year-old boy who presented with skin and skeletal manifestations typical of PDP who also had chronic diarrhea, abdominal pain and weight loss. After giving treatment with risedronate sodium and mesalazine he got significant improvement in his skeletal and abdominal complaints. Bangladesh Med J. 2021 Sept; 50(3): 52-55